1999
DOI: 10.1096/fasebj.13.9002.s216
|View full text |Cite
|
Sign up to set email alerts
|

The mammalian centromere: structural domains and the attenuation of chromatin modeling

Abstract: The centromere‐kinetochore complex can be divided into distinct domains based on structure and function. Previous work has used CREST auto‐antibodies with various microscopic techniques to map the locations of proteins within the centromere‐kinetochore complex and to analyze the maturation of prekinetochores before mitosis. Here we have focused on the centromere‐specific histone Centromere Protein (CENP)‐A and its spatial relationship to other histones and histone modifications found in condensed chromatin. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 43 publications
1
35
0
1
Order By: Relevance
“…Immunostaining with CREST antibody (13) revealed that approximately 80% (n ϭ 100) of multilobulated E145K nuclei contained abnormally clustered centromeres in the region of intense Hoechst staining (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Immunostaining with CREST antibody (13) revealed that approximately 80% (n ϭ 100) of multilobulated E145K nuclei contained abnormally clustered centromeres in the region of intense Hoechst staining (Fig. 2B).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have indicated that histone H3 phosphorylation on serine 10 and serine 28 correlates with mitotic chromosome condensation (Van Hooser et al, 1998;de la Barre et al, 2000;Goto et al, 1999;Sauve et al, 1999). The role of histone phosphorylation during the cell cycle was clearly established in Tetrahymena, where mitosis is restricted to the germ line micronuclei, and transcription is limited to the amitotic macronuclei.…”
Section: Phosphorylationmentioning
confidence: 99%
“…Historically, this approach was useful in identifying the histone H3 variants of centromeric regions employing CREST autoantibodies from scleroderma patients. 15,16 We tested a panel of these mouse mAbs on rapidly growing epichromatin epitope in mitotic chromosomes does not depend upon close proximity of the chromatin to an intact NE or to components of the NE. The epichromatin epitope appears to be an inherent property of chromatin throughout the cell cycle.…”
Section: Introductionmentioning
confidence: 99%